EFEKTIVITAS APLIKASI E-ARSIP PADA KANTOR IMIGRASI KELAS I TPI CILACAP - assiroj, Priati (Polteknik Imigrasi, 2023)
Archives play a crucial role in every institution that carries out public service tasks. Every month, the Cilacap Immigration Office generates approximately a thousand application files from Indonesian citizens. As a result, the process of searching and archiving these files takes a long time, mainly due to the lack of an application provided by the Directorate General of Immigration. Therefore, the Class I TPI Cilacap Immigration Office has developed an innovative solution in the form of an E-Archive application to streamline the archiving process of Indonesian citizen files. The primary objective of developing this E-Archive application is to enhance the productivity of immigration officers in their archiving duties, facilitate the retrieval of required files, and record information for each file. Unlike previous studies that analyzed an E-Archive application called SISUMAKER, this research focuses on analyzing the E-Archive application developed by the Class I TPI Cilacap Immigration Office. The purpose of this research is to evaluate the effectiveness of implementing the E-Archive application in facilitating the tasks of immigration officers and identifying challenges that arise during its implementation. The research methodology used is descriptive-qualitative, with data collected through interviews, observations, and documentation. The research findings indicate that the implementation of the E-Archive application has been effective based on the analysis using five effectiveness indicators. However, there are several challenges in its implementation, such as delays in distributing archives to the TIKKIM Section, insufficient comprehensive features in the E-Archive application, and a lack of notification alerts for every hundred inputted files.